PHONOLOGY OF ACEHNESE REDUPLICATION: APPLYING OPTIMALITY THEORY - Mustafa, Faisal (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Reduplication in Acehnese serves many functions, such as plurality, reciprocity, emphasis, continuity, and repetitions. This word formation process has been previously analyzed in terms of morphology and phonology. The present study aimed to discover the constraint ordering of reduplication to determine the rules that govern each pattern of reduplication in the language. The study employed Correspondence Theory under the umbrella of Optimality Theory, focusing on total and partial reduplication, leaving out rhyming reduplication due to framework limitation. The results show that all patterns of reduplication in Acehnese follow regular application where well-formedness proceeds faithfulness (MAX-IO) and precedes reduplicative identity (MAX-BR). The well-formedness for total reduplication only includes the constraint of the complex nucleus, where a final diphthong in the base changes to a monophthong in the reduplicant. For partial reduplication, the constraint for well-formedness is that the syllable should be open, preceded by a reduplicant size of no more than one syllable, and alignment (either left for reduplicating prefixes or right for reduplicating suffixes). In addition, the well-formedness is proceeded by no insertion (DEP-BR). This study indicates the need to establish a ranking of constraints that govern the phonology of Acehnese outside the context of reduplication, which is a suggestion for future studies.